Entre-temps... brusquement, et ensuite : 12e Biennale de Lyon. - Raspail, Thierry; Boutoux, Thomas; Biennale Lyon 2013; Garait, Nicolas; Kvaran, Danielle; Kvaran, Gunnar B. (Dijon : Les presses du réel, 2013)
de Andrade, Jonathan ; Atkins, Ed ; Baga, Trisha ; Barney, Matthew ; Beloufa, Neïl ; Bibby, Gerry ; Bonneviot, Juliette ; Seshee Bopape, Dineo ; Bruce High Quality Foundation ; Catala, Antoine ; Cha, Xavier ; Chan, Paul ; Cheng, Ian ; Colen, Dan ; Cortright, Petra ; Dodge, Jason ; Domanović, Aleksandra ; Douard, David ; Edvardsen, Mette ; Errò ; Ethridge, Roe ; Fornieles, Ed ; Friõriksdóttir, Gabriela ; Gober, Robert ; Haendel, Karl ; Hamadeh, Rana ; Hervé, Louise ; Maillet, Chloé ; Hyber, Fabrice ; Kaino, Glenn ; Kelsey, John ; Koons, Jeff ; Kukama, Donna ; Lee, Margaret ; Abeles, Michele ; Lennox-Boyd, Patricia ; Lertxundi, Laida ; aalliicceelleessccaannnnee&ssoonn... ; Lislegaard, Ann ; Lowman, Nate ; Madeln Company (Xu Chen) ; Magid, Václav ; Marten, Helen ; Melgaard, Bjarne ; Martins de Melo, Thiago ; Minami, Takao ; Mokgosi, Meloko ; Nazareth, Paulo ; Ono, Yoko ; Pariset, Aude ; Nimer Pjota, Paulo ; Prouvost, Laure ; Reynaud Dewar, Lili ; Richards, James ; Robak, Tabor ; Robbe-Grillet, Alain ; Ronay, Matthew ; Sachs, Tom ; Sagri, Georgia ; Sawa, Hiraki ; Sibande, Mary ; Singh, Alexandre ; Singh, Sumakshi ; Speridião, Gustavo ; Strachan, Tavares ; Takekawa, Nobuaki ; Trecartin, Ryan ; Fitch, Lizzie ; Wächtler, Peter ; Weinberger, Hannah ; Wong, Ming ; Wretman, Helga ; Fudong, Yang ; Zhengzhong, Yang ; Yi, Anicka ; Ding, Zhang
12e Biennale de Lyon du 12 septembre 2013 au 05 janvier 2014
boek